Continuous improvement project within Kaizen: critical success factors in hospitals. Issue 4 (11th June 2018) - Gonzalez-Aleu, Fernando; Van Aken, Eileen M.; Cross, Jennifer; Glover, Wiljeana J.
Abstract : Purpose: Evidence suggests that hospitals are having problems achieving continuous improvement project (CIP) goals or sustaining their results. Therefore, the purpose of this paper is to identify those critical success factors (CSFs) most strongly related to CIP success in hospitals (Lean-Kaizen project, Lean Six Sigma project, Six Sigma projects, and Quality Improvement projects). Design/methodology/approach: A retrospective survey was applied to any CIP leaders/facilitators from hospitals that conducted at least one CIP during the last two years. Findings: Three main findings were obtained from the 116 valid responses. First, the level of importance of 47 out of 53 CSFs to achieve CIPs success in hospitals was assessed as very important or higher (4 or higher on a six-point scale). Second, there are important differences between the CSFs to achieve CIP success in hospitals in this research and previous investigations. Third, the type of CIP affects the level of importance of 16 out of 53 CSFs to achieve CIP success in hospitals. Originality/value: Practitioners involved with CIPs activities in hospitals could use the knowledge extracted from this investigation to improve the impact of their CIPs. Future research should continue in two lines: test if the 53 CSFs for CIPs measure a unique factor and identify the main relationships or paths between CSFs for CIPs and CIP outcomes.